Our superior complex shadow is under a microscope - Edwards, Fiona (My University, 2021)
From the institution of slavery to current waves of systemic oppression, Black people continue to be negatively impacted. This calls attention to the pervasiveness of racism, specifically the anti-Black racism that contorts and constrains Black peoples’ lives. The magnitude of anti-Black racism punctuated human consciousness on a global scale after the public brutal killing of George Floyd, an African-American man in police custody. This poem is inspired by Floyd’s death and the emotional trauma and pain it ignited in Black people around the world. It illustrates the vulnerability of the Black community in respect to ongoing systemic oppression, the inferiorization of Blackness, and the corresponding suffering Black people must endure.
Keywords: racism; anti-Black racism; systemic oppression; Black Lives Matter; racial trauma